Soft science contributions toward nation building - Dahlan Ismail (Universiti Utara Malaysia Press, 2010)
This book begins by unlocking the conceptual domains of sof science. In order to come to terms with soft science, this book present a compilation of seven captains notes which were deliberated at the first International Soft Science Conference 2009 held in Kuala Lumpur.